A Prospective Evaluation of the Reliability and Utility of Quality of Life Measures in Patients With Hepatocellular Carcinoma. (July 2019) - Kim, Gi-Ae; Kim, Ha Il; Chang, Seheon; An, Jihyun; Lee, Danbi; Lee, Han Chu; Han, Seungbong; Shim, Ju Hyun
Abstract : Objectives: Little is known about how quality of life (QOL) can assist clinical decision-making for patients with hepatocellular carcinoma (HCC). This study aimed to investigate the reliability and validity of QOL as well as its prognostic value and utility. Materials and Methods: A prospective cohort of 300 HCC patients at various stages was recruited from 2015 to 2017 in Korea. The subjects answered the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core-30 (QLQ-C30) and QLQ-HCC18 and the Functional Assessment of Cancer Therapy-Hepatobiliary (FACT-Hep) questionnaire. Prognostic nomograms including the QOL scales were developed. The prediction performance of the Barcelona Clinic Liver Cancer (BCLC) and the American Joint Committee on Cancer (AJCC) staging systems when they were incorporated with QOL was investigated. Results: The EORTC QLQ-C30 and QLQ-HCC18 subscales showed higher reliability than FACT-Hep subscales. With regard to the validity, both questionnaires discriminated the patients by stages, treatment modalities, and performance status effectively. Multivariable analysis revealed that EORTC role functioning and EORTC appetite loss subscales were statistically associated with overall survival and disease progression. The developed nomograms accurately estimated the 1-year overall survival and disease progression–free rates. Incorporating the EORTC role functioning subscale or Hepatobiliary Cancer Subscale of FACT-Hep with the BCLC and AJCC systems improved the prognostic classification. Incorporating QOL into the AJCC system showed better predictive accuracy than incorporating performance status into it did. Conclusions: The findings suggest that QOL data can serve as a reliable predictive factor and assist prognostic calculation for HCC patients. Abstract : Supplemental Digital Content is available in the text.